PEMBANGUNAN BERKELANJUTAN DAN PERAN MASYARAKAT SIPIL - Primahendra, Riza (UI Scholars Hub, 2002)
Sustainable development, which in recent times has become a global dialectics, in essence is a critique of various theories concerning modern development. Sustainable development is a concept in favour of the balance between economic, social, and environmental dimensions of development. The balancing process potentially can be achieved through the conception of civil society as an arena in which individuals, state institutions, market and society interact within a framework based on rights through the processes of catalyst of dialogue, balancing interest, picking-up signals, and collective action